Monitoramento autônomo de para-raios de ZnO - Wagner Antonio Moreira Ursine (2013)
Reducing operating costs and improving quality of the provided services, based on better management and consequent increased availability of assets, are key points for electricity companies. Therefore, in the context of power substations, it is necessary to carry out periodic inspections to assess the equipments state of degradation. In particular, the surge arrester appears as a protective device against overvoltages, preventing surges from reaching assets that are sensitive or of great importance to the system. Thermography and leakage current analysis are the techniques adopted for monitoring and diagnosing metal-oxide surge arresters, providing a set of complementary information. In this work, experiments were performed to determine the influence of factors such as temperature, solar radiation and wind speed in the measurement of surface temperature of this device. In addition, a technique is proposed for extracting the resistive portion of the total leakage current. The goal of the presented studies is to help building an information database about diagnosis and monitoring of the equipment found in power substations. This database will be used in an autonomous inspection system. Results show that the proposed methodology for obtaining the resistive current is liable to field implementation, providing a simple and robust technique, especially regarding the harmonics present in operating voltage. The temperature measurement by thermography proved to be very dependent on the amount of solar radiation and room temperature, a fact that was not confirmed for the wind speed. Regarding the infrared camera parameters, emissivity and average reflected temperature were considered crucial for the correct surge arrester temperature measurement.